Multi-element metal alloy nano-particle / biochar composite nano-catalyst rich in vacancy defects and preparation method of multi-element metal alloy nano-particle / biochar composite nano-catalyst

By introducing transition metal elements such as Ni, Al, Zn into the electrolytic hydrogen production catalyst, and regulating the catalyst structure using their corrosion characteristics, a multi-metal alloy nanoparticle/biochar composite catalyst rich in vacancy defects was prepared, which solved the problem of limited improvement in performance of a single metal-based catalyst, and achieved an efficient and environmentally friendly electrolytic hydrogen analysis catalytic effect.

CN119685860AInactive Publication Date: 2025-03-25CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411873050.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The performance improvement of existing single metal-based catalysts is limited, the catalyst specific surface area and active sites are insufficient, and the preparation process of multi-metal alloy catalysts is complex.

Method used

By introducing transition metal elements such as Ni, Al, Zn, etc., and regulating the structure of the catalyst using their corrosion characteristics, a multi-metal alloy nanoparticle/biochar composite catalyst rich in vacancy defects is prepared, so that the alloy nanoparticles are anchored in situ on the surface of N-doped biomass carbon material, and the effective specific surface area of ​​the catalyst and the number of exposed active sites are increased through selective corrosion.

Benefits of technology

The catalytic activity and stability are improved, and the prepared catalyst has high catalytic activity, good stability, simple process, convenient operation and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685860A_ABST
    Figure CN119685860A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element metal alloy nanoparticle / charcoal composite catalyst rich in vacancy defects and a preparation method thereof, and belongs to the field of energy catalysis. The preparation method is formed by anchoring alloy nanoparticles rich in vacancy defects on the surface of an N-doped biomass charcoal material in situ, and comprises the following steps: (1) dipping the biomass material in a multi-metal compound aqueous solution, and freeze-drying to obtain a precursor; (2) performing high-temperature heat treatment on the precursor, and grinding to obtain an alloy nanoparticle / biochar composite material; and (3) putting the composite material into acid or alkali with a proper concentration, stirring at a constant temperature, washing to be neutral, and drying to obtain a material, namely the composite catalyst rich in vacancy defects. The method is simple in process, easy to control and low in cost. In the catalyst, the biomass charcoal material is doped with nitrogen in situ, the alloy nanoparticles are rich in vacancy defects and are uniformly loaded on the carbon carrier, the loading capacity and the grain size are adjustable, the catalytic activity for hydrogen evolution by electrolysis of water is high, the stability is good, and the application prospect in the fields of energy, environment and the like is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy catalytic conversion, and in particular to a multi-metal alloy nanoparticle / biochar composite nanocatalyst rich in vacancy defects and a preparation method thereof. Background Art

[0002] As the pace of global energy structure transformation accelerates, hydrogen energy, as a clean and sustainable energy with great potential, is gradually moving from theoretical exploration to practical application, attracting more and more attention and research investment. Water electrolysis hydrogen production technology is a key method to achieve large-scale hydrogen production, in which the performance of the catalyst plays a vital role in reaction efficiency and energy consumption. Traditional catalyst design mostly relies on single metal materials, but its application is restricted due to the limited metal resources and high cost. In order to promote industrial applications, exploring new catalyst materials to improve energy conversion efficiency and reduce energy consumption has become an urgent need for current research.

[0003] Multi-metal alloy catalysts can effectively improve catalytic performance and reduce costs through the synergistic effect between metals, and have become a research hotspot in recent years. The cell wall / membrane structure of biomass materials can form strong bonds with metal ions, and the defect sites formed during carbonization can directly capture metal atoms to achieve stable loading, which has outstanding potential in improving the catalytic activity and stability of catalysts. The present invention introduces transition metal elements such as Ni, Al, and Zn, and uses their corrosion characteristics to regulate the structure of the catalyst to prepare a multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects with excellent catalytic performance, providing a new, efficient, and environmentally friendly catalyst design strategy for the electrolysis of water to produce hydrogen. Summary of the invention

[0004] The purpose of the present invention is to provide a multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects and a preparation method thereof, so as to solve the problems of limited performance improvement of existing single metal-based catalysts, insufficient catalyst specific surface area and active sites, and complex preparation process of multi-metal alloy catalysts.

[0005] To achieve the above object, the present invention:

[0006] A multi-metal alloy nanoparticle / biochar composite nanocatalyst rich in vacancy defects was prepared and synthesized, so that the alloy nanoparticles were in situ anchored on the surface of the N-doped biochar material, and the effective specific surface area of ​​the catalyst and the number of exposed active sites were increased by selective corrosion, thereby improving the catalytic activity. This preparation method has the characteristics of simple process and convenient operation. The obtained alloy nanoparticles rich in vacancy defects are evenly distributed on the N-doped biochar carrier, the particle size is controllable, the catalytic activity for hydrogen evolution in water electrolysis is high, and the stability is good.

[0007] According to the above scheme, the metal nanoparticles are evenly distributed and the particle size is adjustable in the range of 2nm to 10nm.

[0008] According to the above scheme, the multi-metal alloy nanoparticle / biochar composite nanocatalyst rich in vacancy defects has excellent catalytic performance and outstanding stability.

[0009] The present invention also provides a method for synthesizing a multi-metal alloy nanoparticle / biochar composite nanocatalyst rich in vacancy defects by combining an impregnation method, a high-temperature carbonization in-situ reduction technique, and a chemical corrosion method, the steps of which are as follows:

[0010] (1) Prepare an aqueous solution of a multi-metal compound of a certain concentration and ratio. The multi-metal system greater than or equal to binary can be selected as immiscible Pt-Ni, Pt-Pd-Ni, Pt-Pd-Zn, Pt-Pd-Cu-Al, Pt-Pd-Cu-Co-Al, Pt-Pd-Cu-Co-Fe-Al, Pt-Pd-Au-Cr-Cu-Co-Zn, Pt-Pd-Au-Ru-Cr-Cu-Co-Zn, Pt-Pd-Au-Ru-Rh-C r-Cu-Co-Al, Pt-Pd-Au-Ru-Ce-Rh-Cr-Cu-Co-Al, etc., the alloy raw material can be chloroplatinic acid, chloropalladic acid, nickel chloride hexahydrate, zinc chloride tetrahydrate, cupric chloride dihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, etc., the biomass material is immersed in the above solution for 4 hours, the biomass material can be basswood, white radish, etc., and then taken out and placed in a freeze dryer for freeze drying to obtain a multi-metal alloy-biochar precursor material;

[0011] (2) placing the multi-metal alloy-biochar precursor material obtained in step (1) into a corundum crucible, and subjecting it to heat treatment in a tubular furnace with a certain protective atmosphere for 4 hours, wherein the protective atmosphere is any one of argon and nitrogen, and taking out the sample and subjecting it to grinding treatment to obtain a multi-metal alloy nanoparticle / biochar composite material;

[0012] (3) Add the multi-metal alloy nanoparticle / biochar composite material obtained in step (2) into a beaker containing an acid or alkali solution of a certain concentration, stir and react at a constant temperature for 24 hours, take it out after the reaction, wash it by centrifugation with deionized water until it is neutral, and then dry it in an oven for 12 hours to finally obtain a multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects.

[0013] According to the above scheme, the metal compound in the precursor includes but is not limited to chloropalladic acid and copper chloride, and may also be palladium acetylacetonate, copper nitrate trihydrate, and the like.

[0014] According to the above scheme, the biomass material is pretreated, that is, it is immersed in deionized water for 2 hours, and the water is changed every half an hour.

[0015] According to the above solution, the sacrificial element accounts for 30%-80%.

[0016] According to the above scheme, the immersion time is 4 hours.

[0017] According to the above scheme, the freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum degree is 1Pa, and the drying time is 48 hours.

[0018] According to the above scheme, the multi-metal alloy nanoparticle / biochar composite material is obtained from the multi-metal alloy-biochar precursor material under the protection of a certain atmosphere.

[0019] According to the above scheme, the protective atmosphere is any one of argon and nitrogen.

[0020] According to the above scheme, the heat treatment temperature is 700°C-1100°C.

[0021] According to the above scheme, the heating rate is 10°C / min.

[0022] According to the above scheme, the multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects is obtained by reacting the multi-metal alloy nanoparticle / biochar composite material in an acid or alkaline solution of a certain concentration for a period of time.

[0023] According to the above scheme, the acid or alkali solution is hydrochloric acid solution or sodium hydroxide solution.

[0024] According to the above scheme, the concentration of the acid or base is 0.25mol / L-2mol / L.

[0025] According to the above scheme, the constant temperature stirring reaction temperature is 40°C-80°C.

[0026] The present invention has the following advantages:

[0027] (1) The process of raw material preparation, mixed precursor impregnation and heat treatment of the present invention will not cause water pollution, air pollution and other problems, and is a green and environmentally friendly preparation method.

[0028] (2) The preparation process provided by the present invention is simple, easy to operate, and has a low preparation cost. The prepared catalyst has high catalytic activity for hydrogen evolution in water electrolysis and good stability.

[0029] (3) The present invention uses the synergistic effect of multi-metal alloys to promote the improvement of catalytic performance, and prepares multi-metal alloy nanocomposites rich in vacancy defects through selective chemical corrosion, thereby increasing the effective specific surface area of ​​the catalyst and the number of exposed active sites, thereby improving the catalytic activity of the catalyst; in the prepared multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects, the alloy nanoparticles rich in vacancy defects are in situ anchored on the surface of N-doped biochar, are evenly distributed, have adjustable grain size, have high catalytic activity for hydrogen evolution by electrolysis of water, and have good stability, and have broad application prospects in the fields of electrochemistry, energy, and environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a transmission electron microscope photograph of the PtPdNi / biochar composite catalyst rich in vacancy defects provided in Example 1 of the present invention.

[0031] Figure 2 A high-resolution transmission electron microscope photograph of the PtPdNi / biochar composite catalyst rich in vacancy defects provided in Example 1 of the present invention.

[0032] Figure 3 This is the hydrogen evolution polarization curve of the PtPdNi / biochar composite catalyst rich in vacancy defects provided in Example 1 of the present invention.

[0033] Figure 4 This is a transmission electron microscope photograph of the PtPdAl / biochar composite catalyst rich in vacancy defects provided in Example 2 of the present invention.

[0034] Figure 5 A high-resolution transmission electron microscope photograph of the vacancy defect-rich PtPdAl / biochar composite catalyst provided in Example 2 of the present invention.

[0035] Figure 6 This is the hydrogen evolution polarization curve of the PtPdAl / biochar composite catalyst rich in vacancy defects provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0037] Example 1

[0038] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid and nickel chloride (0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid and 0.03 mol / L nickel chloride) with a total metal ion concentration of 0.04 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g basswood slices (thickness 1.5±1 mm, obtained by pretreatment by soaking in deionized water for 2 hours) in the mixed solution for 4 hours;

[0039] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdNi / biochar precursor material. Subsequently, the PtPdNi / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PtPdNi / biochar composite material;

[0040] (3) 0.1 g of PtPdNi / biochar composite material was placed in 15 ml of 0.5 mol / L hydrochloric acid solution and stirred at a constant temperature of 60 °C for 24 h. The acid-corroded PtPdNi / biochar composite material was then centrifuged and washed with deionized water until it was neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PtPdNi / biochar composite catalyst rich in vacancy defects.

[0041] The vacancy-rich PtPdNi / biochar composite catalyst prepared in this example was characterized by TEM. The TEM results of the obtained sample are as follows: Figure 1 As shown in Figure 2, the alloy nanoparticles are uniformly loaded on the biochar. Discontinuous lattice fringes appear in the HRTEM of the sample ( Figure 2 ), which indicates that there are abundant vacancy defects in the prepared alloy nanoparticles.

[0042] The vacancy defect-rich PtPdNi / biochar composite catalyst prepared in this example was placed in a three-electrode system to test its catalytic performance for hydrogen evolution by electrolysis of water. The specific method is as follows: a graphite carbon electrode is used as a counter electrode, a silver chloride electrode containing a saturated potassium chloride solution is used as a reference electrode, a glassy carbon electrode loaded with a vacancy defect-rich PtPdNi / biochar composite catalyst is used as a working electrode, the electrolyte is a 0.5 mol / L H2SO4 acidic solution, and the scanning speed is 100 mV / s. The test results are shown in Figure 2. Figure 3 As shown, when the current density is 100mA / cm 2When the vacancy defect-rich PtPdNi / biochar composite catalyst prepared in this example exhibits excellent electrocatalytic hydrogen evolution performance, the overpotential of which is only 78.7 mV.

[0043] Example 2

[0044] A method similar to that in Example 1 was used to prepare a PtPdAl / biochar composite catalyst rich in vacancy defects.

[0045] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid and aluminum nitrate (0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid and 0.0067 mol / L (40%) aluminum nitrate) with a total metal ion concentration of 0.0167 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g of basswood slices (thickness of 1.5±1 mm, obtained by pretreatment by immersing in deionized water for 2 hours) in the mixed solution for 4 hours;

[0046] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdAl / biochar precursor material. Subsequently, the PtPdAl / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PtPdAl / biochar composite material;

[0047] (3) 0.1 g of PtPdAl / biochar composite material was placed in 15 ml of 0.5 mol / L sodium hydroxide solution and stirred at 60 °C for 24 h. The alkaline-corroded PtPdAl / biochar composite material was then centrifugally washed with deionized water until neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PtPdAl / biochar composite catalyst rich in vacancy defects.

[0048] The vacancy-rich PtPdAl / biochar composite catalyst prepared in this example was characterized by TEM. Figure 4 As shown in the figure, the alloy nanoparticles are uniformly loaded on the biochar, with an average particle diameter of 2.59±0.72nm and discontinuous lattice fringes ( Figure 5 ), which indicates that the prepared PtPdAl alloy nanoparticles are rich in vacancy defects.

[0049] The catalytic performance of the PtPdAl / biochar composite catalyst rich in vacancy defects prepared in this example was tested for hydrogen evolution by electrolysis of water. The test results are as follows: Figure 6 As shown, when the current density is 100mA / cm 2 When the vacancy defect-rich PtPdAl / biochar composite catalyst prepared in this example exhibits excellent electrocatalytic hydrogen evolution performance, the overpotential is only 87.5 mV.

[0050] Example 3

[0051] A PtAl / biochar composite catalyst rich in vacancy defects was prepared using a method similar to Example 1.

[0052] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid and aluminum nitrate (0.006 mol / L chloroplatinic acid and 0.004 mol / L aluminum nitrate) with a total metal ion concentration of 0.01 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g of basswood flakes in the mixed solution for 4 hours;

[0053] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtAl / biochar precursor material. Subsequently, the PtAl / biochar precursor material is loaded into a crucible as a raw material and heat-treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PtAl / biochar composite material;

[0054] (3) 0.1 g of PtAl / biochar composite material was placed in 15 ml of 0.25 mol / L sodium hydroxide solution and stirred at a constant temperature of 60 °C for 24 h. The alkaline-corroded PtAl / biochar composite material was then centrifugally washed with deionized water until it was neutral, placed in an oven to dry for 12 h, and naturally cooled to room temperature. The resulting solid was a PtAl / biochar composite catalyst rich in vacancy defects.

[0055] Example 4

[0056] A PdAl / biochar composite catalyst rich in vacancy defects was prepared using a method similar to Example 1.

[0057] (1) preparing 20 ml of a mixed aqueous solution of chloropalladic acid and aluminum nitrate (0.006 mol / L chloropalladic acid and 0.004 mol / L aluminum nitrate) with a total metal ion concentration of 0.01 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g of basswood flakes in the mixed solution for 4 hours;

[0058] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PdAl / biochar precursor material. Subsequently, the PdAl / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PdAl / biochar composite material;

[0059] (3) 0.1 g of PdAl / biochar composite material was placed in 15 ml of 0.25 mol / L hydrochloric acid solution and stirred at a constant temperature of 40 °C for 24 h. The acid-corroded PdAl / biochar composite material was then centrifuged and washed with deionized water until it was neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PdAl / biochar composite catalyst rich in vacancy defects.

[0060] Example 5

[0061] A method similar to that in Example 1 was used to prepare a PtPdZn / biochar composite catalyst rich in vacancy defects.

[0062] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid and zinc chloride (0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid and 0.0067 mol / L (40%) zinc chloride) with a total metal ion concentration of 0.0167 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g of basswood flakes in the mixed solution for 4 hours;

[0063] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdZn / biochar precursor material. Subsequently, the PtPdZn / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PtPdZn / biochar composite material;

[0064] (3) Take 0.1g of PtPdZn / biochar composite material and place it in 15ml of 0.5mol / L sodium hydroxide solution. Stir it at a constant temperature of 60℃ for 24 hours. Then, centrifuge and wash the alkaline-corroded PtPdZn / biochar composite material with deionized water until it is neutral, place it in an oven to dry for 12 hours, and cool it naturally to room temperature. The resulting solid is a PtPdZn / biochar composite catalyst rich in vacancy defects.

[0065] Example 6

[0066] A method similar to that in Example 1 was used to prepare a PtPdAl / biochar composite catalyst rich in vacancy defects.

[0067] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid and aluminum nitrate (0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid and 0.0067 mol / L (40%) aluminum nitrate) with a total metal ion concentration of 0.0167 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g of basswood flakes in the mixed solution for 4 hours;

[0068] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdAl / biochar precursor material. Subsequently, the PtPdAl / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After cooling naturally to room temperature, the obtained solid is ground. The ground powder is the PtPdAl / biochar composite material;

[0069] (3) Take 0.1g of PtPdAl / biochar composite material and place it in 15ml of 0.5mol / L hydrochloric acid solution. Stir it at a constant temperature of 60℃ for 24 hours. Then, centrifuge and wash the acid-corroded PtPdAl / biochar composite material with deionized water until it is neutral, place it in an oven to dry for 12 hours, and cool it naturally to room temperature. The resulting solid is a PtPdAl / biochar composite catalyst rich in vacancy defects.

[0070] Example 7

[0071] A method similar to that in Example 1 was used to prepare a PtPdCuAl / biochar composite catalyst rich in vacancy defects.

[0072] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid, cupric chloride and aluminum nitrate (0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid, 0.005 mol / L cupric chloride and 0.01 mol / L aluminum nitrate) with a total metal ion concentration of 0.025 mol / L, stirring thoroughly to form a yellow clear solution, and immersing 1.6 g basswood flakes in the mixed solution for 4 hours;

[0073] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdCuAl / biochar precursor material. Subsequently, the PtPdCuAl / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After naturally cooling to room temperature, the obtained solid is ground. The ground powder is the PtPdCuAl / biochar composite material;

[0074] (3) 0.1 g of PtPdCuAl / biochar composite material was placed in 15 ml of 0.5 mol / L sodium hydroxide solution and stirred at a constant temperature of 40 °C for 24 h. The alkaline-corroded PtPdCuAl / biochar composite material was then centrifuged and washed with deionized water until it was neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PtPdCuAl / biochar composite catalyst rich in vacancy defects.

[0075] Example 8

[0076] A method similar to that in Example 1 was used to prepare a PtPdCuCoAl / biochar composite catalyst rich in vacancy defects.

[0077] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid, cupric chloride and aluminum nitrate with a total metal ion concentration of 0.033 mol / L (including 0.008 mol / L of chloroplatinic acid, 0.002 mol / L of chloropalladic acid, 0.005 mol / L of cupric chloride, 0.005 mol / L of cobalt chloride and 0.013 mol / L of aluminum nitrate), stirring the mixture sufficiently to form a yellow clear solution, and immersing 1.6 g of basswood slices (thickness of 1.5±1 mm, obtained by pretreatment by immersing in deionized water for 2 hours) in the mixed solution for 4 hours;

[0078] (2) After impregnation, take out and place in a freeze dryer for freeze drying, the freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdCuCoAl / biochar precursor material. Subsequently, the PtPdCuCoAl / biochar precursor material is loaded into a crucible as a raw material, and heat-treated in a tubular furnace under an Ar protective atmosphere, heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours, and then naturally cooled to room temperature, and the obtained solid is ground, and the ground powder is the PtPdCuCoAl / biochar composite material;

[0079] (3) 0.1 g of PtPdCuCoAl / biochar composite material was placed in 15 ml of 0.75 mol / L sodium hydroxide solution and stirred at a constant temperature of 40 °C for 24 h. The alkaline-corroded PtPdCuCoAl / biochar composite material was then centrifuged and washed with deionized water until it was neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PtPdCuCoAl / biochar composite catalyst rich in vacancy defects.

[0080] Example 9

[0081] A method similar to that in Example 1 was used to prepare a PtPdCuCoNiAl / biochar composite catalyst rich in vacancy defects.

[0082] (1) preparing 20 ml of a mixed aqueous solution of chloroplatinic acid, chloropalladic acid, cupric chloride and aluminum nitrate with a total metal ion concentration of 0.042 mol / L (including 0.008 mol / L chloroplatinic acid, 0.002 mol / L chloropalladic acid, 0.005 mol / L cupric chloride, 0.005 mol / L cobalt chloride, 0.005 mol / L nickel chloride and 0.017 mol / L aluminum nitrate), stirring the mixture sufficiently to form a yellow clear solution, and immersing 1.6 g basswood flakes in the mixed solution for 4 hours;

[0083] (2) After impregnation, take out and place in a freeze dryer for freeze drying. The freezing time is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum is 1Pa, and the drying time is 48 hours. The block material obtained after freeze drying is the PtPdCuCoNiAl / biochar precursor material. Subsequently, the PtPdCuCoNiAl / biochar precursor material is loaded into a crucible as a raw material and heat treated in a tubular furnace under an Ar protective atmosphere. It is heated to 800°C at a heating rate of 10°C / min and kept at this temperature for 2 hours. After naturally cooling to room temperature, the obtained solid is ground. The ground powder is the PtPdCuCoNiAl / biochar composite material;

[0084] (3) 0.1 g of PtPdCuCoNiAl / biochar composite material was placed in 15 ml of 0.75 mol / L sodium hydroxide solution and stirred at a constant temperature of 40 °C for 24 h. The alkaline-corroded PtPdCuCoNiAl / biochar composite material was then centrifuged and washed with deionized water until it was neutral, dried in an oven for 12 h, and naturally cooled to room temperature. The resulting solid was a PtPdCuCoNiAl / biochar composite catalyst rich in vacancy defects.

[0085] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention solves the problems of complex process, insufficient catalyst specific surface area and active sites in the conventional method for preparing hydrogen evolution catalyst by electrolysis of water, and the prepared multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects has excellent electrocatalytic hydrogen evolution performance and good stability.

[0086] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects, characterized in that: It is composed of multi-metal alloy nanoparticles rich in vacancy defects and biochar, and the alloy nanoparticles are in situ anchored on the surface of N-doped biomass carbon materials.

2. The multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects according to claim 1, characterized in that: The multi-element alloy nanocatalyst rich in vacancy defects has different structural changes caused by alloying, resulting in a synergistic effect, and exhibits better electrocatalytic performance than single metal nanocatalysts; the selective chemical corrosion during the preparation process increases the effective specific surface area of ​​the catalyst and the number of exposed active sites, and the catalytic activity of the sample is improved compared with that before corrosion; The particle size of the multi-metal alloy nanoparticles is adjustable in the range of 2nm to 10nm, and the biomass carbon material is doped with N atoms and has a good degree of graphitization.

3. The method for preparing the multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects according to claim 1, characterized in that: Here are the steps: (1) Prepare an aqueous solution of a multi-metal compound of a certain concentration and ratio. The multi-metal system greater than or equal to binary can be selected as immiscible Pt-Ni, Pt-Pd-Ni, Pt-Pd-Zn, Pt-Pd-Cu-Al, Pt-Pd-Cu-Co-Al, Pt-Pd-Cu-Co-Fe-Al, Pt-Pd-Au-Cr-Cu-Co-Zn, Pt-Pd-Au-Ru-Cr-Cu-Co-Zn, Pt-Pd-Au-Ru-Rh-C r-Cu-Co-Al, Pt-Pd-Au-Ru-Ce-Rh-Cr-Cu-Co-Al, etc., the alloy raw material can be chloroplatinic acid, chloropalladic acid, nickel chloride hexahydrate, zinc chloride tetrahydrate, cupric chloride dihydrate, cobalt chloride hexahydrate, aluminum nitrate nonahydrate, cerium nitrate hexahydrate, etc., the biomass material is immersed in the above solution for 4 hours, the biomass material can be basswood, white radish, etc., and then taken out and placed in a freeze dryer for freeze drying to obtain a multi-metal alloy-biochar precursor material; (2) placing the multi-metal alloy-biochar precursor material obtained in step (1) into a corundum crucible, and subjecting it to heat treatment in a tubular furnace with a certain protective atmosphere for 4 hours, wherein the protective atmosphere is any one of argon and nitrogen, and taking out the sample and subjecting it to grinding treatment to obtain a multi-metal alloy nanoparticle / biochar composite material; (3) Add the multi-metal alloy nanoparticle / biochar composite material obtained in step (2) into a beaker containing an acid or alkali solution of a certain concentration, stir and react at a constant temperature for 24 hours, take it out after the reaction, wash it by centrifugation with deionized water until it is neutral, and then dry it in an oven for 12 hours to finally obtain a multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects.

4. The multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects according to claim 1, characterized in that The freezing time in step (1) is 24 hours, the freezing temperature is -40°C to -60°C, the drying vacuum degree is 1 Pa, and the drying time is 48 hours.

5. The multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects according to claim 1, characterized in that The heat treatment temperature in step (2) is between 700°C and 1100°C.

6. The multi-metal alloy nanoparticle / biochar composite catalyst rich in vacancy defects according to claim 1, characterized in that The concentration of the acid or alkali solution in step (3) is 0.25 mol / L-2 mol / L.

Citation Information

Patent Citations

  • Preparation method of nano-particles with nano-grade porous structure

    CN103406128A

  • Platinum group metal alloy nano-particle with porous structure and preparation method thereof

    CN108031832A

  • Controllable preparation method of in-situ autocatalytic three-dimensional network carbon nano material

    CN110589798A

  • Pt / C-N composite electrocatalytic material with efficient hydrogen evolution performance and preparation method thereof

    CN110961131A

  • Method for preparing high-dispersion carbon-supported Pt-based ordered alloy catalyst and catalyst

    CN113600209A